Human health risk assessment of organophosphorus pesticide in rice crop from selected districts of Anzali International Wetland basin, Iran. (May 2017) - Ghanbari, F; Moattar, F; Monavari, SM; Arjmandi, R
Low fertility in rice caused by Chilo suppressalis has led to the use of diazinon to control this pest. Residue of pesticide could penetrate products and also food which can affect public health. The aim of this research was to determine health risk assessment of organophosphorus (OP) pesticide in rice, a strategic crop in Iran. Ninety rice samples were collected from 30 points during harvesting seasons from Rasht Area, Guilan Province, Iran from which 30 samples were prepared. The concentration of diazinon, the most common pesticide used in the study area, was determined by high-performance liquid chromatography. The result indicated that the total average of diazinon in rice samples (31.91 mg/kg) is by far higher than the maximum residue limit recommended by the European Union. According to the results, EDAI was 0.051 mg/kg day, while health risk index in rice was 10.2. Results showed that there is a health risk associated with the lifetime consumption of rice polluted by OP pesticide in the study area.